2018
DOI: 10.3389/fmicb.2018.00095
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus terreus Inhibits Growth and Induces Morphological Abnormalities in Pythium aphanidermatum and Suppresses Pythium-Induced Damping-Off of Cucumber

Abstract: The study investigated the efficacy of two isolates of Aspergillus terreus (65P and 9F) on the growth, morphology and pathogenicity of Pythium aphanidermatum on cucumber. In vitro tests showed that the two isolates inhibited the growth of P. aphanidermatum in culture. Investigating P. aphanidermatum hyphae close to the inhibition zone showed that the hyphae showed abnormal growth and loss of internal content. Treating P. aphanidermatum with the culture filtrate (CF) of A. terreus resulted in significant rise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 87 publications
(98 reference statements)
5
46
0
1
Order By: Relevance
“…These results are in agreement with the findings of Hajlaoui et al (1992) who reported that the yeast like antagonistic fungus (Garg et al 2010). The observed loss of turgidity of hyphae of the pathogenic fungi in the inhibition zone suggests alterations in the permeability of the cell membrane (Halo et al 2018). The hyphal malformations may be attributed to production of antibiotic substances by Bacillus sp.…”
Section: Resultssupporting
confidence: 92%
“…These results are in agreement with the findings of Hajlaoui et al (1992) who reported that the yeast like antagonistic fungus (Garg et al 2010). The observed loss of turgidity of hyphae of the pathogenic fungi in the inhibition zone suggests alterations in the permeability of the cell membrane (Halo et al 2018). The hyphal malformations may be attributed to production of antibiotic substances by Bacillus sp.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies showed that Streptomyces hydrogenans culture filtrates inhibited the growth of Alternaria Brassicicol 31 . Oospore production was greatly decreased in the presence of culture filtrates of 48 P and 28 R. Similar observation was made by 16 , where Aspergillus terreus affected spore production by P . aphanidermatum .…”
Section: Discussionsupporting
confidence: 82%
“…Several endophytic fungi are used as biocontrol agents against plant disease such as Botryosphaeria ribis , Trichoderma sp. and Aspergillus terreus 14,16 . Talaromyces species have multiple benefits for plants; they have been used as biocontrol agents against several plant pathogen 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Ezziyyani et al (2007), while studying the interaction between the pathogenic fungus, Phytophthora capsici and the antagonist, Trichoderma harzianum also observed deformation, disintegration and vacuolization of P. capsici hyphae. The disintegration of hyphae of the pathogenic fungi in the inhibition zone in this study suggests alterations in the permeability of the cell membrane (Halo et al 2018).…”
Section: Discussionmentioning
confidence: 54%